Study of the Form And Meaning of Serwai Ethnic Spell Language - Ongky Gusfika; Irwan Satria; Vebbi Andra (Yayasan Karinosseff Muda Indonesia, 2022)
This study aims to determine the form and meaning of Serwai Ethnic spell language in Tebat Sibun Village, Talo Kecil District, Seluma Regency. In this research, the writers used descriptive research method with qualitative research type. From the results of this study, it can be concluded that those study discusses two problems, namely (1) What is the form of the Serawai Ethnic spell language in Tebat Sibun Village, Talo Kecil District, Seluma Regency (2) What is the meaning of serawai Ethnic mantra language in Tebat Sibun Village, Talo Kecil District, as long as. The results of the first problem research, it is known that there are five existence of the spell language of Serawai Ethnic in Tebat Sibun Village, Talo Kecil District, Seluma Regency (a) experience of spell language which contains elements of treatment (b) experience of spell language which contains elements of self-protection (c) Existence of spell language containing agricultural elements (d) existence of spell language containing elements of attracting women/pellets (e) existence of spell language containing elements of eliminating hatred. The results of the second problem research, it is known that the meaning of the language of the Serawai Ethnic in Tebat Sibun Village, Talo Kecil District, Seluma Regency, there are five meanings (a) the meaning of healing spell language (b) the meaning of self-protective spell language (c) the meaning of agricultural spell language (d) the meaning of language female charm spells/pellets (e) meaning of hate-killing spells.